FABP1 in wonderland. Issue 3 (22nd June 2016) - Prinetti, Alessandro; Mitro, Nico
Abstract : Cannabinoid receptors hold a core position in the brain and control memory, cognition, movement, and pain sensitivity. sn ‐2 arachidonoylglycerol (2‐AG) activates neuronal cannabinoid receptors as a full agonist. The brain may rely on circulating arachidonic acid to synthesize endogenous cannabinoids. This Editorial highlights a study by Martin and coworkers in the current issue of the Journal of Neurochemistry in which the authors describe, for the first time, that liver acts as a pool of arachidonic acid that under certain conditions feeds the brain to produce endocannabinoids. Therapeutics affecting liver FABP1 levels should take into account that FABP1 represents a fatty acid reservoirs for the brain. Read the highlighted article "FABP‐1 gene ablation impacts brain endocannabinoid system in male mice" on page407 . Abstract : Cannabinoid receptors hold a core position in the brain and control memory, cognition, movement, and pain sensitivity. sn ‐2 arachidonoylglycerol (2‐AG) activates neuronal cannabinoid receptors as a full agonist. The brain may rely on circulating arachidonic acid to synthesize endogenous cannabinoids. This Editorial highlights a study by Martin and coworkers in the current issue of the Journal of Neurochemistry in which the authors describe, for the first time, that liver acts as a pool of arachidonic acid that under certain conditions feeds the brain to produce endocannabinoids. Therapeutics affecting liver FABP1 levels should take into account that FABP1 represents a fatty acid reservoirs for the brain. Read the highlighted article "FABP‐1 gene ablation impacts brain endocannabinoid system in male mice" on page407 .